Alopecia‐mental retardation syndrome: Molecular genetics of a rare neuro‐dermal disorder. (21st April 2021) - Muzammal, Muhammad; Ahmad, Safeer; Ali, Muhammad Zeeshan; Khan, Muzammil Ahmad
Abstract: Alopecia‐mental retardation syndrome (APMR) is a rare autosomal recessive neuro‐dermal disorder. It is characterized by heterogeneous phenotypic features, that is, absence of hair on the scalp, eyelashes, and eyebrows and mild to severe intellectual disability. So far, approximately 14 families (i.e., Iranian, Pakistani, and Swiss) with APMR have been reported in the scientific literature. Its precise prevalence is still unknown, but according to a predictive estimate, it prevails with the ratio of 1 in 1, 000, 000 persons worldwide. Until now, only four loci (two characterized and two uncharacterized) have been reported to be involved in APMR. The pathogenic variants in alpha‐2‐HS‐glycoprotein [ AHSG; APMR1 (MIM#203650)] and lanosterol synthase [ LSS; APMR4 (MIM#618840)] are the characterized genetic factors associated with APMR. Among them, AHSG was reported in a consanguineous Iranian family and LSS gene in a Swiss origin family, while the remaining two uncharacterized loci, that is, APMR2 and APMR3, are reported in the Pakistani population. The current mini‐report discusses the molecular genetics and mutational spectrum of APMR syndrome, its differential diagnosis from related disorders, and prediction of plausible candidate genes in two uncharacterized loci.